2020
DOI: 10.1128/mbio.02703-19
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Control of PlsB Is Sufficient To Coordinate Membrane Synthesis with Growth in Escherichia coli

Abstract: Every cell must produce enough membrane to contain itself. However, the mechanisms by which the rate of membrane synthesis is coupled with the rate of cell growth remain unresolved. By comparing substrate and enzyme concentrations of the fatty acid and phospholipid synthesis pathways of Escherichia coli across a 3-fold range of carbon-limited growth rates, we show that the rate of membrane phospholipid synthesis during steady-state growth is determined principally through allosteric control of a single enzyme,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The reactions were performed with nonradioactive substrates, the samples were acid precipitated, and the pellets hydrolyzed with Asp-N protease. This process liberates a tripeptide harboring the prosthetic group and attached acyl chains that were then separated and detected by LC-MS/MS ( 17 , 18 , 19 ). Acetyl-ACP was not detected in assays without MadA and was robustly detected in assays containing MadA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were performed with nonradioactive substrates, the samples were acid precipitated, and the pellets hydrolyzed with Asp-N protease. This process liberates a tripeptide harboring the prosthetic group and attached acyl chains that were then separated and detected by LC-MS/MS ( 17 , 18 , 19 ). Acetyl-ACP was not detected in assays without MadA and was robustly detected in assays containing MadA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes produce acetyl-ACP that was first detected as a component of the ACP thioester pool decades ago based on metabolic labeling and electrophoretic analyses in E. coli ( 5 , 9 ). More recent mass spectrometry methods confirm acetyl-ACP is a major component of the E. coli ACP pool ( 18 , 19 ). The origin of the acetyl-ACP pool has been a mystery, and the discovery of MadA identifies an enzyme responsible for acetyl-ACP synthesis in Proteobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared for acyl-ACP quantification as previously described ( 53 ) with modifications. One milliliter aliquots of cultures at midlog phase growth were removed to a 1.5 ml Eppendorf tube containing 250 μl ice cold 10% trichloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…How membrane synthesis and cell-wall synthesis are linked to biomass growth is a question that remains fundamentally not understood in any bacterium. The first committed steps of fatty-acid and phospholipid synthesis are likely the major pathway elements for the control of membrane synthesis (Cronan Jr and Rock, 2008;Dowhan, 2013;Noga et al, 2020;Rock and Cronan, 1996;Cronan Jr and Waldrop, 2002). However, the signals responsible for controlling their activities largely remain to be identified (Noga et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The first committed steps of fatty-acid and phospholipid synthesis are likely the major pathway elements for the control of membrane synthesis (Cronan Jr and Rock, 2008;Dowhan, 2013;Noga et al, 2020;Rock and Cronan, 1996;Cronan Jr and Waldrop, 2002). However, the signals responsible for controlling their activities largely remain to be identified (Noga et al, 2020). Furthermore, while multiple gene-regulatory feedbacks for cell-wall metabolism have been identified (Patel et al, 2020) Garner (2020) suggested that PrkC senses the availability of lipid II, the precursor of peptidoglycan synthesis, and thus regulates the number of moving MreB filaments.…”
Section: Discussionmentioning
confidence: 99%